2013
DOI: 10.3897/zookeys.320.5352
|View full text |Cite
|
Sign up to set email alerts
|

Aroid scarabs in the genus Peltonotus Burmeister (Coleoptera, Scarabaeidae, Dynastinae): key to species and new distributional data

Abstract: The southeast Asian scarab beetle genus Peltonotus Burmeister (Scarabaeidae, Dynastinae, Cyclocephalini) is reviewed. New country records for Peltonotus morio Burmeister (Myanmar and Vietnam), Peltonotus nasutus Arrow (southern China and Cambodia), and Peltonotus favonius Jameson and Wada (Myanmar) are reported, including a new record in the Palearctic/Sino-Japanese biogeographic region. The first female specimen of Peltonotus favonius is described. Biological associations with aroid inflorescences are reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Morón and Ratcliffe (1996) transferred the genus Coscinocephalus from Cyclocephalini to Pentodontini based on characters of the head, mouthparts, and parameres shared with Orizabus Fairmaire, 1878. The work of Mary Liz Jameson, while focused mainly on the subfamily Rutelinae, has altered the concept of Cyclocephalini (Jameson 1998, Jameson et al 2002, Jameson and Wada 2004, 2009, Jameson and Jákl 2010, Jameson and Drumont 2013). Two genera, Acrobolbia Ohaus, 1912 and Peltonotus , previously classified in Rutelinae were transferred into Cyclocephalini based on morphological phylogenetic analyses (Jameson 1998, Jameson et al 2002, Jameson and Wada 2004).…”
Section: Nomenclatural and Taxonomic History Of The Cyclocephaline Scmentioning
confidence: 99%
See 1 more Smart Citation
“…Morón and Ratcliffe (1996) transferred the genus Coscinocephalus from Cyclocephalini to Pentodontini based on characters of the head, mouthparts, and parameres shared with Orizabus Fairmaire, 1878. The work of Mary Liz Jameson, while focused mainly on the subfamily Rutelinae, has altered the concept of Cyclocephalini (Jameson 1998, Jameson et al 2002, Jameson and Wada 2004, 2009, Jameson and Jákl 2010, Jameson and Drumont 2013). Two genera, Acrobolbia Ohaus, 1912 and Peltonotus , previously classified in Rutelinae were transferred into Cyclocephalini based on morphological phylogenetic analyses (Jameson 1998, Jameson et al 2002, Jameson and Wada 2004).…”
Section: Nomenclatural and Taxonomic History Of The Cyclocephaline Scmentioning
confidence: 99%
“…Morphological phylogenetic analysis of Rutelina (Rutelinae: Rutelini) suggested that Peltonotus were more closely related to Cyclocephalini than Rutelini (Jameson 1998). Subsequent works on the genus have treated Peltonotus as a member of Cyclocephalini (Jameson and Wada 2004, 2009, Jameson and Jákl 2010, Jameson and Drumont 2013). …”
Section: Generic Overviewsmentioning
confidence: 99%
“…In several genera of the Rhaphidophora clade (Epipremnum, Monstera, Rhaphidophora, Scindapsus; sensu Cusimano et al, 2011; Fig. 1), the inflorescence mimics the Aroideae kettle traps and enables these plants to have almost the same pollination mechanism and similar pollinator groups as in Aroideae (Sultana et al, 2006;Chouteau et al, 2007;Toda & Lakim, 2011;Fartyal et al, 2013;Jameson & Drumont, 2013;Gibernau, 2016;Prieto & Cascante-Marín, 2017). Maybe the spathe also serves to concentrate sunlight to the center of the inflorescence (i.e., the spadix) and to slightly raise the temperature there, which helps insects to heat up and which facilitates the emission of floral volatiles, especially in species belonging to the two temperate genera Lysichiton and Symplocarpus.…”
Section: Discussionmentioning
confidence: 99%
“…Jameson&Wada , 2009;Jameson & Drumont, 2013 Trichogomphus galeatus Dechambre, 1996Kanchanaburi Dechambre, 1996 Trichogomphus lunicollis Burmeister, 1847…”
Section: Phetchabununclassified
“…Among them, over 200 species are found in Southeast Asia. Thirty-two species have been recorded from Thailand (Arrow, 1910;Arrow, 1914;Endrodi, 1969;Endrodi, 1978;Mizunuma, 1999;Dechambre, 1996;Ek-Amnuay, 2002;Rowland, 2006;Rowland, 2011;Jameson & Wada, 2009;Jameson & Drumont, 2013;Jakl & Zidek, 2015; Table 1).…”
Section: Introductionmentioning
confidence: 99%